Revisiting the Experiential Effect: How Criminal Offending Affects Juveniles’ Perceptions of Detection Risk - Kaiser, Florian (Journal of developmental and life-course criminology, 2022)
Perceptual deterrence research has consistently found that criminal offending is inversely related to subsequent perceptions of the risk of being caught or arrested. This inverse relationship has been dubbed an “experiential effect,” reflecting the idea that people learn by committing (undetected) crimes that the detection or arrest risk is lower than first feared. The current study explores the validity of this experiential argument. It relies on self-report data from 3,259 adolescent participants in the panel study Crime in the modern City (Duisburg, Germany). We computed detection rates and risk perceptions, and used fixed effects models to investigate the proposed experiential learning process. Most findings support the experiential argument: (1) juvenile offenses were rarely detected by the police, (2) juveniles (especially those inexperienced with crime) tended to overestimate the detection risk, (3) juveniles reduced their risk perceptions when they committed crimes, (4) this reduction occurred primarily among those who overestimated the detection risk in periods when they were not committing crimes. However, the study also produced the surprising finding that the experiential effect seems to be short-lived: people appeared to return to initial risk perception levels when they stopped committing crimes. Overall, the results corroborate the experiential argument. However, they also indicate that the argument may need revision to account for the potential short-term nature of the experiential effect. This “ephemerality effect” is good news for policy, as lowered risk perceptions will in most cases only temporarily increase the likelihood of future delinquency.